The relationship between oral health and confidence of medan city residents after the COVID-19 booster vaccination: a descriptive study - Pasaribu, Melania Theresia; Zubaedah, Cucu; Suwargiani, Anne Agustina; Kadir, Rahimah Binti Abdul (Padjadjaran Journal of Dental Researchers and Students, 2024)
ABSTRACT Introduction: The governments globally, including in Indonesia, aimed to return to pre-pandemic conditions via widespread vaccination. Indonesia mandated full and booster doses. The pandemic had impacted oral health, leading to increased stress and difficulties in oral cavity checks. This study investigated the link between dental/oral health and confidence in Medan City post-COVID-19 booster vaccination. Methods: The study was a descriptive correlational research on oral health's connection to confidence among Medan City residents who had received a COVID-19 vaccine booster. It employed non-probability sampling with convenience samples. The respondents were individuals who completed an online Google Form questionnaire. The research took place from May to June 2023, and the relationship between dental/oral health and confidence was analyzed using the Spearman correlation test. Results: The gathered data that met the population criteria consisted of 460 individuals. 412 (89.6%) individuals were categorized as having good oral health, while 448 (97%) were categorized as having good self-confidence. There was a positive and moderate correlation between oral health and self-confidence in the people of Medan City after receiving the COVID-19 booster vaccine, with a Spearman correlation coefficient of p=0.363. There was a positive correlation between oral health and self-confidence in the people of Medan city after receiving the COVID-19 booster vaccine. Conclusion: The relationship between oral health and confidence in health of Medan City residents after the COVID-19 booster vaccination based on this study was a positive correlation with moderate strength.KEY WORDS: dental health, community, confidence, post vaccination, COVID-19, booster.Hubungan kesehatan gigi dan mulut dengan kepercayaan diri masyarakat kota medan pasca vaksin COVID-19 taraf booster: studi deskriptifABSTRAK Pendahuluan: Pemerintah secara global, termasuk di Indonesia, bertujuan untuk kembali ke kondisi sebelum pandemi melalui vaksinasi massal. Indonesia mewajibkan dosis penuh dan dosis penguat. Pandemi telah berdampak pada kesehatan gigi dan mulut, meningkatkan stres dan kesulitan dalam pemeriksaan rongga mulut. Studi ini menyelidiki hubungan antara kesehatan gigi/mulut dan kepercayaan diri masyarakat di Kota Medan setelah vaksinasi penguat COVID-19. Metode: Studi ini merupakan penelitian deskriptif korelasional tentang hubungan antara kesehatan gigi dan mulut dengan rasa percaya diri di antara penduduk kota Medan yang telah menerima vaksin booster COVID-19. Penelitian ini menggunakan teknik sampling non-probabilitas dan convenience. Responden penelitian adalah individu yang telah menyelesaikan kuesioner Formulir Google secara daring. Penelitian ini dilakukan dari Mei hingga Juni 2023. Hubungan antara kesehatan gigi/mulut dan rasa percaya diri dianalisis menggunakan uji korelasi Spearman. Hasil: Data yang terkumpul yang memenuhi kriteria terdiri dari 460 individu. Sejumlah 412 (89,6%) individu dikategorikan memiliki kesehatan gigi yang baik, sedangkan 448 (97%) dikategorikan memiliki kepercayaan diri yang baik. Terdapat korelasi positif dan sedang antara kesehatan gigi dan kepercayaan diri di masyarakat Kota Medan setelah menerima vaksin booster COVID-19, dengan koefisien korelasi Spearman p=0,363. Terdapat korelasi positif antara kesehatan gigi dan kepercayaan diri di masyarakat Kota Medan setelah menerima vaksin booster COVID-19. Simpulan: Hubungan antara kesehatan gigi dan kepercayaan diri penduduk Kota Medan setelah menerima vaksin booster COVID-19 memiliki korelasi positif dengan kekuatan sedang. KATA KUNCI: kesehatan gigi, masyarakat, kepercayaan diri, pasca vaksin, COVID-19, booster.